2014
DOI: 10.1097/mat.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Thoratec CentriMag for Temporary Treatment of Refractory Cardiogenic Shock or Severe Cardiopulmonary Insufficiency

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 48 publications
1
39
1
5
Order By: Relevance
“…The incidence of EGF has increased slightly in recent years, probably due to the shortage of organs and the consequent extensive use of marginal donors with high α‐agonist or inotropic dosages . Reported rates of EGF after Htx range from 2.3 to 28.2%, with mortality rates ranging from 20 to 66% , which is in line with our data.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The incidence of EGF has increased slightly in recent years, probably due to the shortage of organs and the consequent extensive use of marginal donors with high α‐agonist or inotropic dosages . Reported rates of EGF after Htx range from 2.3 to 28.2%, with mortality rates ranging from 20 to 66% , which is in line with our data.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of EGF has increased slightly in recent years, probably due to the shortage of organs and the consequent extensive use of mar-ginal donors with high a-agonist or inotropic dosages (1,2). Reported rates of EGF after Htx range from 2.3 to 28.2%, with mortality rates ranging from 20 to 66% (1)(2)(3)(4)(5)(6)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), which is in line with our data. Such a wide range of incidence represents wide ranges in definitions and types of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic literature review and meta-analysis of observational studies conducted by Borisenko et al [25] included 53 publications with data of a total of 999 patients. The authors reported the survival rate while on support as 62-83%, and 30-day survival as 41-66%, depending on the placement indication.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the various centrifugal pump designs can have significant effects on hemodynamic performance . PediMag and CentriMag pumps have been successfully used in pediatric and adult patients requiring Ventricular Assist Device (VAD) and ECMO support . They have similar magnetically levitated, bearingless impellers and utilize the same hardware platform (motor and console) .…”
Section: Introductionmentioning
confidence: 99%